2016
DOI: 10.1523/jneurosci.0839-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Supratrigeminal Bilaterally Projecting Neurons Maintain Basal Tone and Enable Bilateral Phasic Activation of Jaw-Closing Muscles

Abstract: Anatomical studies have identified brainstem neurons that project bilaterally to left and right oromotor pools, which could potentially mediate bilateral muscle coordination. We use retrograde lentiviruses combined with a split-intein-mediated split-Cre-recombinase system in mice to isolate, characterize, and manipulate a population of neurons projecting to both the left and right jaw-closing trigeminal motoneurons. We find that these bilaterally projecting premotor neurons (BPNs) reside primarily in the supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…5a ). Retrograde-lentivirus infects axons and is transported back to cell bodies 36 , 37 . Ai65 is a Cre and Flp co-dependent tomato reporter 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a ). Retrograde-lentivirus infects axons and is transported back to cell bodies 36 , 37 . Ai65 is a Cre and Flp co-dependent tomato reporter 38 .…”
Section: Resultsmentioning
confidence: 99%
“…CANE-LV-Cre (titer, 5×10 8 ifu/ml; pLenti-hSynapsin-Cre-WPRE [Addgene Plasmid #86641]; CANE-LV envelope [Addgene Plasmid #86666]) and CANE-RV-mCherry (titer, 5×10 8 ifu/ml) were produced as previously described 12 . FuGB2-coated RG-LV-hSyn-FlpO and RG-LV-hSyn-DIO-FlpO were produced and concentrated as described previously 36 . pAAV-SynP-DIO-TVA-EGFP-RG (pAAV-SynP-DIO-sTpEpB) 28 was packaged in serotype AAV2/rh8 by the University of Pennsylvania Vector Core.…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by a past study (Chiala et al, 1992), we found that parvalbumin (Pv) is expressed in excitatory (glutamatergic) SpVIr neurons. To determine whether Pv+ SpVIr cells represent the premotor neurons that project to both Po thalamus and extrinsic facial motoneurons, we employed a split-Cre system (Wang et al, 2012; Stanek et al, 2016). Specifically, we generated Pv-CreN knockin mice, and injected retrograde lentivirus that expressies CreC (RG-LV-CreC) in Po in Pv-CreN; Ai14 (Cre-dependent tdTomato reporter) double transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…RG-LV-CreC and RG-LV-Cre were designed and produced as described (Stanek et al, 2016). AAV2/8-hSyn-Flex-TeLC-P2A-GFP was designed and produced as described (Zhang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation